A Comparative study of durability property on compact tension specimen with unique CFRP and inhomogeneous iron through analysis - Ho Lee, Jung; Ung Cho, Jae (International Journal of Engineering and Technology, 2018)
Most damage of mechanical structures is due to cracks within the structure. This study is to develop the design of safer structures with strength characteristics by material. We have performed 3D modeling for compact tension specimen such as CFRP material, stainless steel and aluminum alloy, and stainless steel and copper alloy as inhomogeneous material. The boundary conditions are applied to each CFRP and compact tension specimen model with inhomogeneous material and the identical conditions are also applied to each specimen model. The simulation tension analysis has been carried for this study to investigate the strength characteristic. The inhomogeneous material in mechanical structure can be maximized with durability and material strength combined with the advantages of each metal. The material used for these mechanical structures is an essential factor. CFRP made of carbon fiber has been received the attention for a high level of durability and lightweight characteristics. If we apply CFRP material to mechanical structures, we may reduce deformation and stress that occurs, maximize durability of mechanical structures, and prevent deformation and damage. Comparing each specimen model, we can consider the CFRP compact tension specimen model to be the most suitable material for real application as its maximum deformation and maximum equivalent stress turned out to be lower than the other inhomogeneous material specimen models. We could find out that although it is a single material, it possesses a stronger durability and strength characteristic compared to inhomogeneous material combined with the advantages of each material. In this study, the durability and strength characteristics of specimen models are thought to be improved by applying simulation analysis after designing compact tension models for each material.
Keywords: Strength; CFRP Material; Inhomogeneous Material; Compact Tension Specimen; Durability